High strength steel composite galvanized sheet resistant to spot weld LME cracking and its preparation method
Patent Information
- Application Number
- JP2024548605
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-17
- Filing Date
- 2023-02-17
- Publication Date
- 2025-03-11
AI Technical Summary
【0044】 本発明は、高強度鋼本体の表面に軟鋼複合層を複合圧延することで、スポット溶接時に液体亜鉛が粒界に沿って母材に浸透するのを回避し、高強度鋼複合亜鉛メッキ板のスポット溶接LME敏感性を低下させ、スポット溶接LME割れの発生を効果的に回避し、スポット溶接LME割れ問題を緩和し、高強度鋼本体の抵抗スポット溶接性能を向上させ、スポット溶接継手の機械的特性を著しく改善する。
Smart Images

Figure 2025506533000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite high strength steel sheet and a preparation method thereof, in particular to a high strength steel composite galvanized sheet resistant to spot weld LME (liquid metal embrittlement) cracking and a preparation method thereof. [Background technology]
[0002] The research, development and application of lightweight materials for automobiles are related to various aspects such as energy conservation, exhaust gas reduction, safety and cost, and are of great significance to global energy conservation, resource conservation and environmental protection, becoming a leading direction in the development of automotive materials. High strength materials such as AHSS (advanced high tensile steel) are fully demonstrating their great potential for reducing the weight of automobiles with the aim of saving energy.
[0003] To improve the corrosion resistance of high strength steels, galvanizing processes such as hot-dip galvanizing and electro-galvanizing are widely used. The use of galvanized high strength steel sheets in automotive applications inevitably requires joining techniques, but galvanized high strength steel sheets are prone to liquid metal embrittlement (LME) during subsequent hot working, such as hot stamping and resistance spot welding, which is one of the main barriers to the use of galvanized high strength steel sheets in the automotive field.
[0004] The characteristic of LME cracking is that when the base material is in contact with another kind of liquid metal, i.e., hot-dip galvanized layer, under externally applied stress or internal stress caused by restraint force, thermal expansion, phase transition, etc., the liquid metal will penetrate along the grain boundaries of the base material, and in severe cases, cracks will form and the plasticity of the base material will be reduced. Contact between the LME-sensitive base material and liquid metal, stress, and appropriate temperature range are the three necessary conditions for LME crack formation, and when high-strength steel galvanized sheets are resistance spot welded, the above three conditions may be met simultaneously, so the problem of spot weld LME cracking of high-strength steel galvanized sheets is particularly serious. These steel grades are generally characterized by the presence of retained austenite, high strength, and relatively high carbon, silicon, and manganese contents, among which second-generation AHSS and third-generation AHSS are the most sensitive to spot weld LME.
[0005] China invention patent CN201610963996.5 discloses a method for resistance spot welding of galvanized high strength steel with good joint properties, which uses three welding pulses in one spot welding cycle. The first and second welding pulses are used to generate molten nuclei and inhibit the occurrence of LME cracking. The first welding pulse generates molten nuclei with a diameter of 3.75T1 / 2-4.25T1 / 2. The second welding pulse makes the nuclei grow slowly. The third welding pulse is a slow cooling pulse to improve the plasticity of the weld spot. Although this method minimizes the time and extent to which the conditions necessary to induce LME exist in spot welded joints through optimization of the spot welding process, it cannot completely eliminate the causes of LME.
[0006] Chinese invention patent CN201810819361.7 discloses a multi-layer steel and a method for reducing liquid metal embrittlement, the multi-layer steel including a core formed from a transformation induced plasticity (TRIP) steel. A decarburized layer is disposed on at least one side of the outside of the core. The decarburized layer has a reduced carbon content relative to the core. A zinc-based layer is disposed on the outside of the decarburized layer. The decarburized layer may be composed of at least 80% ferrite, so that LME is reduced or mitigated. This method can only reduce the problem of LME cracking to a certain extent, and has problems such as the thickness and uniformity of the decarburized layer not being easily controlled, and the surface properties of the base material becoming unstable.
[0007] Chinese invention patent CN201780080831.6 discloses a multi-layer galvanized alloy steel with excellent spot weldability and corrosion resistance, which includes a steel substrate and a multi-layer plating layer formed on the steel substrate, each plating layer of the multi-layer plating is a Zn plating layer, an Mg plating layer, and a Zn-Mg alloy plating layer, and the ratio of the weight of Mg contained in the multi-layer plating layer to the total weight of the multi-layer plating layer is 0.13-0.24. In this method, it is difficult to ensure the adhesion between the plating layer and the substrate, and it is difficult to control the stability and uniformity of the plating layer due to the complex phase transition of the Zn-Mg alloy. Summary of the Invention [Problem to be solved by the invention]
[0008] An object of the present invention is to provide a high-strength steel composite galvanized sheet having low spot weld LME sensitivity and resistance to spot weld LME cracking, and to improve the resistance spot welding performance of the high-strength steel composite galvanized sheet.
[0009] Another object of the present invention is to provide a method for preparing a high-strength steel composite galvanized sheet resistant to spot-weld LME cracking, which can reduce the spot-weld LME sensitivity of the high-strength steel composite galvanized sheet by composite rolling of a mild steel composite layer while ensuring the performance of the base material, and alleviate the problem of spot-weld LME cracking. [Means for solving the problem]
[0010] The present invention is realized as follows: A high-strength steel composite galvanized plate resistant to spot weld LME cracking, comprising a high-strength steel body, a mild steel composite layer and a galvanized layer, wherein two mild steel composite layers are composite-rolled onto two surfaces of the high-strength steel body, respectively, and a galvanized layer is formed on at least one surface of the mild steel composite layer to form a high-strength steel composite galvanized plate.
[0011] Here, the high strength steel body is a high strength steel susceptible to spot weld LME and may contain C, Si and Mn, and may further contain Ti and Cr, and optionally contain one or more elements such as Nb, B and Al, the balance being Fe and unavoidable impurities such as P and S.
[0012] In some embodiments, the high strength steel body has, in mass percent, C≧0.10%, Mn≧1.0%, and Si≧0.07%. In some embodiments, the high strength steel body has, in mass percent, C≧0.14%, Mn≧1.5%, and Si≧0.4%. In some embodiments, the high strength steel body has, in mass percent, C: 0.14-0.60%, Mn: 1.5-16%, and Si: 0.07-2.0%. In some embodiments, the high strength steel body has, in mass percent, C: 0.14-0.30%, Mn: 1.5-3.5%, and Si: 0.4-2.0%.
[0013] When the high-strength steel body contains Ti and Cr, the Ti content can be ≧0.01%, for example, 0.01 to 0.10% or 0.01 to 0.05%, and the Cr content can be ≧0.01%, for example, 0.01 to 0.10% or 0.01 to 0.05%.
[0014] Optionally, the high strength steel may further contain 0-0.06% Nb, 0-0.005% B, and 0-2.0% Al.
[0015] High strength steels typically contain ≦0.01% P and ≦0.01% S as impurities. In some embodiments, the high strength steel of the present invention contains C: 0.1-0.3%, Si: 0.4-2.50%, Mn: 1.0-11.0%, and Al: 0-2.0%.
[0016] As used herein, high strength steel refers to steel having a tensile strength of ≥ 780 MPa, preferably ≥ 980 MPa, more preferably ≥ 1180 MPa. In some embodiments, high strength steel as used herein has a tensile strength of 780-1500 MPa, preferably 1180-1500 MPa.
[0017] High strength steels known in the art can be used to practice the present invention. Exemplary high strength steels can be selected from one or more of QP steel, TRIP steel, DH steel, 7Mn steel, 10Mn steel, and MS steel. Exemplary QP steels can include C: 0.1-0.25%, Si: 0.4-2.50%, Mn: 1.50-3.00%, and Al: 0.03-1.10%. Exemplary TRIP steels can include C: 0.15-0.3%, Si: 0.6-2.0%, Mn: 1.6-2.5%, and Al: 0.02-0.90%. Exemplary DH steels can include C: 0.12-0.21%, Si: 0.3-0.9%, Mn: 1.6-2.5%, and Al: 0.02-0.60%. An exemplary 7Mn steel may include C: 0.1-0.3%, Si: 0.1-2.0%, Mn: 6-8%, and Al: 1-2%. An exemplary 10Mn steel may include C: 0.1-0.3%, Si: 0.1-2.0%, Mn: 9-11%, and Al: 1-2%. An exemplary MS steel may include C: 0.1-0.3%, Si: 0.1-0.5%, and Mn: 1.0-1.8%. These steels may include components known in the art to be included in such steels.
[0018] In some embodiments, the steel used for the high strength steel body is a high strength steel that is sensitive to spot weld LME, the high strength steel body comprising, in mass percent, C≧0.14%, Mn≧1.5%, Si≧0.4%, and having a tensile strength≧780 MPa, wherein the steel used for the mild steel composite layer is a mild steel that is insensitive to spot weld LME, the mild steel comprising, in mass percent, C:≦0.1%, Mn:≦1.1%.
[0019] In some embodiments, the mild steel composite layer comprises C and Mn, with a C content of ≦0.1%, a Mn content of ≦0.7%, and a tensile strength of ≦590 MPa, in mass percent.
[0020] In some embodiments, the mild steel contains, in mass percent, C: 0.001 to 0.1%, and Mn: 0.1 to 1.1%.
[0021] In some embodiments, the mild steel contains, in mass percent, C: 0.001-0.1%, Si: 0.001-0.50%, Mn: 0.1-0.1.1%, Nb: 0-0.02%, Ti: 0-0.025%, Ni: 0-0.025%, Cr: 0-0.05%, P:≦0.05%, and the balance being Fe and unavoidable impurities.
[0022] In some embodiments, the mild steel contains C: 0.001-0.08%, Si: 0.001-0.05%, Mn: 0.1-0.7%, Nb: 0-0.02%, Ti: 0-0.025%, Ni: 0-0.025%, Cr: 0-0.05%, P:≦0.05%, and the balance being Fe and unavoidable impurities.
[0023] In some embodiments, the mild steel may be selected from one or more of IF steel, aluminum killed steel, cold rolled carbon structural steel, phosphorus-added high strength steel, bake hardening steel (BH steel), and low alloy steel, which are well known in the art. An exemplary IF steel may include C: 0.001-0.01%, Mn: 0.10-1.00%. An exemplary aluminum killed steel may include C: 0.01-0.1%, Mn: 0.1-0.5%. An exemplary BH steel may include C: 0.002-0.1%, Mn: 0.10-1.00%. An exemplary low alloy steel may include C: 0.02-0.1%, Mn: 0.5-1.1%, and Si: 0.05-0.5%.
[0024] In some embodiments, the tensile strength of the mild steel used in the present invention is in the range of 150 to 590 MPa. In some embodiments, the tensile strength of the mild steel used in the present invention is in the range of 150 to 340 MPa.
[0025] The green slab thickness of the high strength steel body and the green slab thickness of the mild steel composite layer must satisfy the relationship L×A+M×B+N×C=T.
[0026] Here, A is the ratio of the green slab thickness of one mild steel composite layer to the thickness of the composite slab, C is the ratio of the green slab thickness of the other mild steel composite layer to the thickness of the composite slab, and B is the ratio of the green slab thickness of the high strength steel body to the thickness of the composite slab, and A+B+C=100%. The composite slab is the total thickness of the green slabs of the high strength steel body and the two mild steel composite layers.
[0027] L is the tensile strength of one of the mild steel composite layers after annealing, N is the tensile strength of the other mild steel composite layer after annealing, and M is the tensile strength of the high strength steel body after annealing.
[0028] T is the target tensile strength of the high strength steel composite galvanized plate. Here, the unit of the tensile strength is MPa, and the unit of the thickness is microns.
[0029] In the high strength steel composite galvanized plate, the thicknesses of the two mild steel composite layers may or may not be the same.
[0030] In the high strength steel composite galvanized sheet, the two mild steel composite layers may or may not have the same composition.
[0031] In the above-mentioned high-strength steel composite zinc-plated sheet, the thickness of each mild steel composite layer is 10 to 200 μm, preferably 20 to 200 μm.
[0032] In the high-strength steel composite zinc-plated sheet, the zinc-plated layer has a thickness of 4 to 26 μm. In the above-mentioned high-strength steel composite zinc-plated sheet, the preferred values of A:B and C:B are within the range of 1:35.5 to 1:5.
[0033] The resistance of the high-strength steel composite zinc-plated plate to spot welding LME cracking means that there are no LME cracks in the joint before welding spatter occurs, and that after welding spatter occurs, the length of Type A LME cracks does not exceed 10% of the plate thickness and the number of LME cracks does not exceed 6, the length of Type D LME cracks does not exceed 3% of the plate thickness and the number of LME cracks does not exceed 3, and there are no Type B or Type C LME cracks.
[0034] In some embodiments, the high strength steel composite galvanized sheet has a yield strength > 680 MPa, a tensile strength > 980 MPa, and an elongation > 12%.
[0035] 1. A method for preparing a high strength steel composite galvanized sheet resistant to spot weld LME cracking, comprising the steps of: Step 1: take the raw slab of high-strength steel body and the raw slabs of two mild steel composite layers, attach the raw slabs of the two mild steel composite layers to two surfaces of the raw slab of high-strength steel body, and weld the ends of the raw slabs of the two mild steel composite layers to the ends of the raw slab of high-strength steel body to form a composite slab; Step 2: The composite slab is heated through a plate splitting process to reduce its thickness, and then subjected to initial rolling. Then, the raw slab of the high-strength steel body and the raw slab of the two mild steel composite layers are metallurgically bonded together to form a slab with a tensile strength of T through hot rolling, pickling, cold rolling, and annealing in sequence; Step 3: Coating at least one side of the slug with a galvanized layer to form a high-strength steel composite galvanized plate.
[0036] In step 1, before the green slab of the two mild steel composite layers 2 is laminated with the green slab of the high strength steel body 1, the lamination surfaces of the high strength steel body 1 and the two mild steel composite layers 2 need to be sanded and cleaned.
[0037] The method of coating the galvanized layer includes hot dip galvanizing or electroplating.
[0038] The above-mentioned hot rolling, pickling, cold rolling, annealing, hot plating and electroplating can be carried out by methods well known in the art. For example, an exemplary hot rolling process includes heating the slag to 1200-1280°C, holding for 0.5-4 hours, hot rolling at a final rolling temperature of 850°C-1000°C, and then cooling to 400-650°C at a rate of 30-100°C / s and coiling.
[0039] The deformation amount of the cold rolling can be controlled to usually be 35 to 75%, for example, 50 to 75%. An exemplary annealing may include heating at a rate of 1-20°C / sec to a soaking temperature of 800-830°C with a soaking hold time of 30-240 seconds, then cooling to 650-750°C at a rate of 2-20°C / sec (e.g., 3-10°C / sec), then cooling to 250-350°C at a rate of 20-80°C / sec and holding for 10-120 seconds. In some embodiments, the material is heated to a soaking temperature at a rate of 1 to 20°C / sec, the soaking temperature is 800 to 830°C, the soaking holding time is 30 to 180 seconds, then cooled to 650 to 750°C at a rate of 3 to 10°C / sec, then cooled to 280 to 300°C at a rate of 20 to 80°C / sec and held for 10 to 120 seconds, then heated to 450 to 470°C at a rate of 5 to 20°C / sec and held for 200 to 300 seconds. In some embodiments, the material is heated to a soaking temperature at a rate of 1 to 20°C / sec, the soaking temperature is 810 to 830°C, the soaking holding time is 30 to 240 seconds, the dew point temperature is controlled to -50 to 20°C, and then cooled to 650 to 720°C at a rate of 2 to 20°C / sec, and then cooled to 250 to 350°C at a rate of 20 to 80°C / sec and held for 10 to 120 seconds.
[0040] Exemplary hot dip galvanizing includes a galvanizing temperature of 440-500° C. and a galvanizing time of 5-200 seconds. After galvanizing, the steel is cooled to room temperature at a cooling rate of 20° C. / second or faster.
[0041] It should be understood that the appropriate hot rolling, pickling, cold rolling, annealing, hot dip galvanizing / electroplating processes can be selected depending on the high strength steel or mild steel used.
[0042] Compared with the prior art, the present invention has the following advantages: 1. The present invention uses a mild steel composite layer that is insensitive to spot welding LME cracking on two surfaces of a high-strength steel body by composite rolling. During spot welding, the mild steel composite layer acts as a barrier to prevent liquid zinc from penetrating into the base material of the high-strength steel body along the grain boundary, fundamentally solving the problem of spot welding LME cracking of the high-strength steel body, ensuring the mechanical properties of the base material, while achieving good resistance spot welding performance and very low spot welding LME sensitivity.
[0043] 2. When the high-strength steel composite galvanized plate of the present invention is spot welded, there is no LME crack in the joint before the generation of welding spatter, and after the generation of welding spatter, the length of Type A LME cracks does not exceed 10% of the plate thickness and the number of LME cracks does not exceed 6, the length of Type D LME cracks does not exceed 3% of the plate thickness and the number of LME cracks does not exceed 3, and there is no LME cracks of Type B or Type C. Its basic welding performance and the mechanical properties of the base material meet the application requirements of automobile manufacturing and other related fields.
[0044] The present invention uses composite rolling of a mild steel composite layer on the surface of a high-strength steel body, thereby avoiding the penetration of liquid zinc into the base material along the grain boundary during spot welding, reducing the spot welding LME sensitivity of the high-strength steel composite galvanized plate, effectively avoiding the occurrence of spot welding LME cracking, mitigating the spot welding LME cracking problem, improving the resistance spot welding performance of the high-strength steel body, and significantly improving the mechanical properties of the spot welded joint. [Brief description of the drawings]
[0045] [Figure 1] FIG. 1 is a cross-sectional view of a high strength steel composite galvanized sheet resistant to spot weld LME cracking according to the present invention. [Diagram 2] FIG. 2 shows the spot weld LME evaluation results (crack length) of a high-strength steel-galvanized composite sheet in Example 1 of a high-strength steel-galvanized composite sheet resistant to spot weld LME cracking according to the present invention. [Diagram 3] FIG. 3 shows the spot weld LME evaluation results (number of cracks) of a high-strength steel-galvanized composite sheet in Example 1 of a high-strength steel-galvanized composite sheet resistant to spot weld LME cracking according to the present invention. [Figure 4] FIG. 4 shows the spot weld LME evaluation results (crack length) of the control example of Example 1. [Diagram 5] FIG. 5 is a graph showing the hardness distribution of a spot-welded joint in Example 1 of the high-strength steel composite zinc-plated sheet resistant to spot-welded LME cracking according to the present invention, in which:
number
number
[0046] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. Although not shown separately, the steel composition targeted in this specification complies with the composition range specified in GB / T 13304.1-2008.
[0047] Referring to the attached Fig. 1, the high strength steel composite galvanized plate resistant to spot weld LME cracking includes a high strength steel body 1, a mild steel composite layer 2 and a zinc-plated layer 3, the two mild steel composite layers 2 being compositely rolled onto two surfaces of the high strength steel body 1, respectively, and a zinc-plated layer 3 being formed on at least one surface of the mild steel composite layer 2 to form a high strength steel composite galvanized plate. Since spot weld LME sensitivity differs depending on the type of steel, and spot weld LME cracking occurs on the surface of zinc-plated high strength steel, the composite rolling of the mild steel composite layer 2 can reduce the spot weld LME cracking sensitivity of the surface of the high strength steel body 1, and fundamentally solve the occurrence of spot weld LME cracking.
[0048] The high strength steel body 1 is a high strength steel susceptible to spot weld LME, containing, in mass percent, C≧0.14%, Mn≧1.5%, Si≧0.4%, the balance being Fe, other alloying elements and impurity elements, and having a tensile strength≧780 MPa. The high strength steel body 1 may be any high strength steel that is susceptible to spot weld LME, such as QP (Quenching and Partitioning), TRIP (transformation induced plasticity steel), TWIP (twinning induced plasticity steel), DH (dual-phase high ductility steel), 7Mn (Fe-7%Mn-0.3%C-2%Al), 10Mn (Fe-10%Mn-0.3%C-2%Al), DP (dual-phase steel), MS (Martensitic Steel), and other steel types.
[0049] The mild steel composite layer 2 is mild steel that is insensitive to spot welding LME, contains C and Mn, and has, in mass percent, a C content ≦0.1%, a Mn content ≦0.7%, and a tensile strength ≦590 MPa, such as IF steel (interstitial-free steel), aluminum killed steel, BH steel (Bake Hardenable steel), low alloy steel, etc.
[0050] The green slab thickness of the high strength steel body 1 and the green slab thickness of the mild steel composite layer 2 must satisfy the relational expression LxA+MxB+NxC=T.
[0051] Here, A is the ratio of the green slab thickness of one mild steel composite layer 2 to the composite slab thickness, C is the ratio of the green slab thickness of the other mild steel composite layer 2 to the composite slab thickness, and B is the ratio of the green slab thickness of the high strength steel body 1 to the composite slab thickness, and A+B+C=100%. The composite slab has a thickness equal to the total of the green slab thicknesses of the high strength steel body 1 and the two mild steel composite layers 2.
[0052] L is the tensile strength of one of the mild steel composite layers 2 after annealing, N is the tensile strength of the other mild steel composite layer 2 after annealing, and M is the tensile strength of the high strength steel body 1 after annealing.
[0053] T is the target tensile strength of the high strength steel composite galvanized plate. In the high-strength steel composite zinc-plated sheet, the thickness of each mild steel composite layer 2 is 10 to 200 μm. The thicknesses of the two mild steel composite layers 2 on both sides of the high-strength steel body 1 may be the same or different.
[0054] In the high-strength steel composite zinc-plated sheet, the zinc-plated layer 3 has a thickness of 4 to 26 μm.
[0055] 1. A method for preparing a high strength steel composite galvanized sheet resistant to spot weld LME cracking, comprising the steps of: Step 1: Take a raw slab of high strength steel body 1 and a raw slab of two mild steel composite layers 2, attach the raw slabs of the two mild steel composite layers 2 to two surfaces of the raw slab of high strength steel body 1, and weld the ends of the raw slabs of the two mild steel composite layers 2 to the ends of the raw slab of high strength steel body 1 to form a composite slab.
[0056] Before the green slab of the two mild steel composite layers 2 is laminated with the green slab of the high strength steel body 1, the laminated surfaces of the high strength steel body 1 and the two mild steel composite layers 2 need to be sanded and cleaned to ensure a smooth finish.
[0057] Step 2: The composite slab is heated through a thick plate splitting process to reduce its thickness, and initial rolling is performed, after which steps such as hot rolling, pickling, cold rolling, and annealing are sequentially performed to metallurgically bond the raw slab of the high-strength steel body 1 and the raw slab of the two mild steel composite layers 2 to form a slug with tensile strength T. The steps such as initial rolling, hot rolling, pickling, cold rolling, and annealing are adopted from existing manufacturing processes, and therefore their explanation will not be repeated here.
[0058] Step 3: Coat at least one side of the slug with a zinc-coated layer 3 by hot-dip galvanization, electroplating or other means to form a high-strength steel composite zinc-coated plate. The zinc-coated layer 3 can be coated by hot-dip galvanization, electroplating or other existing processes, and the description will not be repeated here.
[0059] In order to evaluate the spot welding LME susceptibility of the high-strength steel composite galvanized sheet of the present invention, the Rapid LME Test Procedure for Coated Sheet Steels V2.0 standard issued by the North American Automotive / Steel Partnership (A / SP) was used. In this standard, cracks are classified into Type A, Type B, Type C, and Type D based on the distribution location of the cracks. Type A cracks exist at the contact area between the tip of the spot welding electrode and the steel sheet on the top and bottom surfaces of the spot welded joint, and the standard requires that the length of the Type A crack before the occurrence of welding spatters is ≦10% of the sheet thickness, and there is no provision in the standard for the length of the Type A crack after the occurrence of welding spatters. Type B cracks exist at the non-contact area between the spot welding electrode and the steel sheet on the top and bottom surfaces of the spot welded joint, and the standard requires that the length of the Type B crack is ≦5% of the sheet thickness regardless of whether the welding spatters are generated or not. Type C cracks exist at the contact area between the top and bottom steel sheets of the spot welded joint, and the standard requires that the length of the Type C crack is ≦5% of the sheet thickness regardless of whether the welding spatters are generated or not. Type D cracks exist in the shoulders of the depressions on the top and bottom surfaces of spot welded joints, where the deformation of the weld thickness is greatest. The standards require that the length of a Type D crack before the generation of weld spatter be ≦5% of the plate thickness, and that the length of a Type D crack after the generation of weld spatter be ≦10% of the plate thickness.
[0060] The high-strength steel composite galvanized sheet of the present invention has good resistance to resistance spot welding LME cracking, which means that there is no LME cracking in the joint before the generation of welding spatter, and that after the generation of welding spatter, the length of Type A LME cracks does not exceed 10% of the plate thickness and the number of LME cracks does not exceed 6, the length of Type D LME cracks does not exceed 3% of the plate thickness and the number of LME cracks does not exceed 3, and there is no LME cracking of Type B or Type C. At the same time, the basic welding performance and the mechanical properties of the base material of the high-strength steel composite galvanized sheet of the present invention meet the application requirements in related fields.
[0061] Example 1 Referring to FIG. 1 , a raw slab of QP1180 (as high strength steel body 1) was taken. The raw slab of high strength steel body 1 contained, in mass percent, 0.18% C, 1.67% Si, 2.73% Mn, 0.0089% P, 0.0009% S, 0.02% Ti, 0.03% Cr, and the balance being iron and unavoidable impurity elements.
[0062] A green slab of IF steel DC04 (as mild steel composite layer 2) was taken. The green slab of mild steel composite layer 2 contained, in mass percent, 0.0015% C, 0.002% Si, 0.114% Mn, 0.0119% P, 0.0044% S, and the balance being iron and unavoidable impurity elements.
[0063] The thickness of the green slab of the two mild steel composite layers 2 was the same, both 24 mm, and the thickness of the green slab of the high strength steel body 1 was 182 mm. The thickness ratio of the green slab of the high strength steel body 1 to the green slab of the mild steel composite layer 2 (one sheet) was 7.5:1, and in this embodiment, A=C=10.5%, L=N=150 MPa, B=79%, M=1250 MPa, and T=1019 MPa. The green slabs (with the same thickness) of the two mild steel composite layers 2 were composite-rolled onto two surfaces of the green slab of the high strength steel body 1 through the processes of composite slab formation, thick plate division, hot rolling, pickling, cold rolling, and annealing to obtain slag, and the two surfaces of the slag were coated with the zinc-coated layer 3 by hot dip galvanization to form a high strength steel composite zinc-coated plate. The specific process was as follows: (1) Hot rolling: The slag was heated to 1200 and held for 0.5 hours, then hot rolled at a final rolling temperature of 850°C, cooled to 400°C at a speed of 30°C, and coiled.
[0064] (2) Cold rolling: The deformation amount of cold rolling was 50%. (3) Annealing: Heat at a rate of 5°C / sec to a soaking temperature of 800°C, hold for 50 seconds, cool at a rate of 3°C / sec to 650°C, then cool at a rate of 20°C / sec to 280°C, hold for 20 seconds, then heat at a rate of 5°C / sec to 450°C, hold for 200 seconds.
[0065] (4) Hot-dip galvanizing: The galvanizing temperature was 450° C., and the galvanizing time was 20 seconds. After galvanizing, the steel was cooled to room temperature at a cooling rate of 20° C. / second or more.
[0066] The final high-strength steel composite galvanized plate had a total thickness of 1.5 mm, with the two mild steel composite layers 2 having a thickness of approximately 160 μm and the galvanized layer 3 having a thickness of approximately 8.6 μm. The high-strength steel composite galvanized plate had a yield strength of 696 MPa, a tensile strength of 1074 MPa and a fracture elongation of 15%, meeting the requirements of QP980GI, and the structure of the central layer was that of QP steel, containing martensite and retained austenite.
[0067] The spot welding LME susceptibility of the composite rolled high strength steel galvanized sheet in this example was evaluated using the Rapid LME Test Procedure for Coated Sheet Steels V2.0 standard issued by A / SP. When the welding current was ≧11kA, welding spatter occurred, and as shown in Figures 2 and 3, there was no LME crack in the joint before the welding spatter occurred, and after the welding spatter occurred, the length of the LME crack of Type A did not exceed 10% of the plate thickness, the number of cracks did not exceed 6, the length of the LME crack of Type D did not exceed 3% of the plate thickness, the number of cracks did not exceed 3, and there were no LME cracks of Type B and Type C. According to this standard, the high strength steel galvanized sheet in this example was a spot welding LME low susceptible material.
[0068] A 1.5 mm thick QP980GI material was used as a control. The composition of the QP980GI material was, in mass percent, 0.18% C, 1.8% Si, 2.3% Mn, 0.001% S, 0.012% P, 0.017% Ti, and the balance was iron and unavoidable impurities. Mechanical properties of the QP980GI material: Yield strength was 687 MPa, tensile strength was 1068 MPa, and elongation at break was 22%. Spot weld LME susceptibility evaluation of QP980GI material was performed using the Rapid LME Test Procedure for Coated Sheet Steels V2.0 standard. When the welding current is ≥ 10.5kA, welding spatter occurs, and Type A cracking after spattering is allowed as shown in Figure 4. Therefore, the evaluation results of the control QP980GI material did not include Type A cracking, but Type D cracking with a length close to 90% of the plate thickness and Type C cracking with a length exceeding 20% of the plate thickness occurred. This material was classified as spot weld LME sensitive material according to this standard.
[0069] Using the spot welding parameters shown in Table 1, the basic performance of spot welding was tested for this embodiment and a control example, and the hardness distribution of the spot welded joints is shown in FIG.
[0070] [Table 1]
[0071] As can be seen from Fig. 5, the weldable section of the high-strength steel composite galvanized plate of this example was 6.6kA to 9.0kA, with a section width of 2.4kA, while the weldable section of the QP980GI material of the control example was 6.7kA to 9.1kA, with a section width of 2.4kA, and the weldable sections of both were equivalent. The lower limit of the weldable section was the welding current corresponding to a molten nucleus diameter of 5mm, and the upper limit of the weldable section was the minimum welding current corresponding to the occurrence of welding spatter. Correspondingly, when the molten core diameter of both samples was 5 mm, the joint TSS (Tensile Shear Strength) strength and joint CTS (Cross Tension Strength) strength of both samples were measured. The joint TSS strength of this example was 13.89 kN (this joint TSS strength value was the average value of the three samples measured in this example), and the joint CTS strength was 6.22 kN (this joint CTS strength value was the average value of the three samples measured in this example), while the joint TSS strength of the control example was 14.033 kN (this joint TSS strength value was the average value of the three control example samples measured), and the joint CTS strength was 4.277 kN (this joint CTS strength value was the average value of the three control example samples measured). Thus, the TSS strength of the joint in this example was equivalent to that of the control example, but the presence of the IF steel in the composite rolled layer reduced the carbon equivalent in the molten nucleus region, resulting in a decrease in the hardness of the molten nucleus and an increase in the plasticity of the molten nucleus, and therefore the CTS strength of the joint in this example was significantly improved compared to the control example.
[0072] Example 2 Referring to FIG. 1 , a raw slab of QP1180 (as high strength steel body 1) was taken. The raw slab of high strength steel body 1 contained, in mass percent, 0.18% C, 1.67% Si, 2.73% Mn, 0.0089% P, 0.0009% S, 0.02% Ti, 0.03% Cr, and the balance being iron and unavoidable impurity elements.
[0073] A green slab of IF steel DC04 (as mild steel composite layer 2) was taken. The green slab of mild steel composite layer 2 contained, in mass percent, 0.0015% C, 0.002% Si, 0.114% Mn, 0.0119% P, 0.0044% S, and the balance being iron and unavoidable impurity elements.
[0074] The raw slab of the high-strength steel body 1 and the raw slab of the mild steel composite layer 2 (the raw slabs of the mild steel composite layer 2 on both sides have the same thickness) were made into composite slabs with thickness ratios of 5.5:1, 7.5:1, 10.5:1, 16.5:1 and 35.5:1 (these ratios are the ratios between the thickness of the raw slab of the high-strength steel body 1 and the thickness of one raw slab of the mild steel composite layer), respectively, and high-strength steel composite galvanized sheets with different thicknesses of the mild steel composite layer 2 were obtained through the processes of composite slabization, thick plate division, hot rolling, pickling, cold rolling, annealing, hot-dip galvanizing, etc., by the preparation method of the present invention. The detailed information of each high-strength steel composite galvanized sheet (1# to 5#) is shown in Table 2. The specific processes were as follows: (1) Hot rolling: The slag was heated to 1230°C and held for 1 hour, then hot rolled at a final rolling temperature of 920°C, cooled to 550°C at a rate of 50°C / s, and coiled.
[0075] (2) Cold rolling: The deformation amount of cold rolling was 60%. (3) Annealing: Heat at a rate of 10°C / sec to a soaking temperature of 810°C, hold for 100 seconds, cool at a rate of 7°C / sec to 700°C, then cool at a rate of 50°C / sec to 300°C, hold for 80 seconds, then heat at a rate of 15°C / sec to 470°C, hold for 300 seconds.
[0076] (4) Hot-dip galvanizing: The galvanizing temperature was 480° C., and the galvanizing time was 100 seconds. After galvanizing, the steel was cooled to room temperature at a cooling rate of 20° C. / second or more.
[0077] [Table 2]
[0078] The spot weld LME susceptibility of 1#~5# high strength steel composite galvanized plate was evaluated using the Rapid LME Test Procedure for Coated Sheet Steels V2.0 standard issued by A / SP. As a result, as shown in Table 3, there were no LME cracks in the spot welded joints of 1#~5# high strength steel composite galvanized plate before welding spatter occurred. After welding spatter occurred, there were no LME cracks of Type B and Type C in the spot welded joints of 1#~5# high strength steel composite galvanized plate, the length of LME cracks of Type A did not exceed 10% of the plate thickness, the number of cracks did not exceed 6, and the length of LME cracks of Type D did not exceed 3% of the plate thickness, and the number of cracks did not exceed 3.
[0079] [Table 3]
[0080] Example 3 Referring to FIG. 1 , a raw slab of QP1180 (as high strength steel body 1) was taken. The raw slab of high strength steel body 1 contained, in mass percent, 0.18% C, 1.67% Si, 2.73% Mn, 0.0089% P, 0.0009% S, 0.02% Ti, 0.03% Cr, and the balance being iron and unavoidable impurity elements.
[0081] Cold-rolled carbon structural steel St37-2G, phosphorus-added high-strength steel HC220P, high-strength IF steel HC180Y, bake-hardened steel HC180B, and low-alloy high-strength steel HC300LA were taken as green slabs of mild steel composite layer 2. The main chemical compositions of the above five types of green slabs of mild steel composite layer 2 are shown in Table 4 in mass percent, with the remainder being iron and unavoidable impurity elements.
[0082] [Table 4]
[0083] A green slab of high-strength steel body 1 and a green slab (one sheet) of the above five types of mild steel composite layer 2 were made into a composite slab with a thickness ratio of 7.5:1, and high-strength steel composite galvanized sheets 6# to 10# having different mild steel composite layers 2 were obtained through the processes of composite slab making, thick plate division, hot rolling, pickling, cold rolling, annealing, hot-dip galvanizing, etc. according to the preparation method of the present invention. Detailed information of each high-strength steel composite galvanized sheet (6# to 10#) is shown in Table 5. The specific process was as follows: (1) Hot rolling: The slag was heated to 1250°C and held for 2 hours, then hot rolled at a final rolling temperature of 980°C, cooled to 630°C at a rate of 90°C / s, and coiled.
[0084] (2) Cold rolling: The deformation amount of cold rolling was 70%. (3) Annealing: Heat at a rate of 20°C / sec to a soaking temperature of 830°C, hold for 160 seconds, cool at a rate of 8°C / sec to 750°C, then cool at a rate of 70°C / sec to 300°C, hold for 100 seconds, then heat at a rate of 15°C / sec to 470°C, hold for 200 seconds.
[0085] (4) Hot-dip galvanizing: The galvanizing temperature was 500° C., and the galvanizing time was 180 seconds. After galvanizing, the steel was cooled to room temperature at a cooling rate of 20° C. / second or more.
[0086] [Table 5]
[0087] The spot weld LME susceptibility of the 6#~10# high strength steel composite galvanized plate composite rolled in this example was evaluated using the Rapid LME Test Procedure for Coated Sheet Steels V2.0 standard issued by A / SP. The results showed that there were no LME cracks in the spot welded joints of the 6#~10# high strength steel composite galvanized plate before welding spatter occurred. After welding spatter occurred, there were no LME cracks of Type B and Type C in the spot welded joints of the 6#~10# high strength steel composite galvanized plate, the length of the LME cracks of Type A did not exceed 10% of the plate thickness, the number of cracks was 6 or less, and the length of the LME cracks of Type D was 3% or less of the plate thickness, and the number of cracks did not exceed 3.
[0088] Example 4 Referring to FIG. 1 , a raw slab of DH980 (as high strength steel body 1) was taken. The raw slab of high strength steel body 1 contained, in mass percent, 0.18% C, 0.48% Si, 2.4% Mn, 0.021% Cr, 0.04% Nb, 0.02% Ti, 0.0004% B, 0.009% P, 0.001% S, 0.23% Al, and the balance being iron and unavoidable impurity elements.
[0089] As the raw slabs of mild steel composite layer 2, IF steel DC04, cold-rolled carbon structural steel St37-2G, phosphorus-added high-strength steel HC220P, high-strength IF steel HC180Y, and bake-hardened steel HC180B were taken. The main chemical compositions of the above five types of raw slabs of mild steel composite layer 2 are shown in Table 6 in mass percent, with the balance being iron and unavoidable impurity elements.
[0090] [Table 6]
[0091] The raw material of the slab of each composite layer was rolled in proportion to the thickness of 7.5:1 (the ratio of the thickness of the high-strength steel body to the thickness of one mild steel slab) and prepared for use. The adjacent interfaces of each composite layer were cleaned to remove impurities such as oxide scale. The boundaries of each contacting composite layer were welded and sealed, and the oxygen between the composite layers was removed by vacuum drawing, and then the composite slab was rolled. Through the following hot rolling, pickling, cold rolling, annealing and hot-dip galvanizing processes, high-strength steel composite galvanized sheets 11#~15# with different mild steel composite layers 2 were obtained, and the detailed information of each high-strength steel composite galvanized sheet (11#~15#) is shown in Table 7.
[0092] (1) Hot rolling: The slag was heated to 1280°C and held for 4 hours, then hot rolled at a final rolling temperature of 950°C, cooled to 600°C at a rate of 80°C / s, and coiled.
[0093] (2) Pickling (3) Cold rolling: The deformation amount of cold rolling was 40%.
[0094] (4) Annealing: The material was heated to a soaking temperature of 810°C at a rate of 15°C / sec, the soaking time was 200 seconds, and the dew point temperature was controlled at 0°C. The material was then cooled to 670°C at a rate of 10°C / sec, and then cooled to 320°C at a rate of 60°C / sec, and held for 80 seconds.
[0095] (6) Hot-dip galvanizing: The galvanizing temperature was 450°C, and the galvanizing time was 1600 seconds. After galvanizing, the steel was cooled to room temperature at a cooling rate of 20°C / second or more.
[0096] [Table 7]
[0097] The spot weld LME susceptibility of the 6#~10# high strength steel composite galvanized plate composite rolled in this example was evaluated using the Rapid LME Test Procedure for Coated Sheet Steels V2.0 standard issued by A / SP. The results showed that there were no LME cracks in the spot welded joints of the 11#~15# high strength steel composite galvanized plate before welding spatter occurred. After welding spatter occurred, there were no Type B and Type C LME cracks in the spot welded joints of the 11#~15# high strength steel composite galvanized plate, the length of the LME cracks of Type A did not exceed 10% of the plate thickness, the number of cracks was 6 or less, and the length of the LME cracks of Type D was 3% or less of the plate thickness, and the number of cracks did not exceed 3.
[0098] The above is merely a preferred embodiment of the present invention, and does not limit the scope of protection of the invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention are included in the scope of protection of the present invention.
Claims
1. A high-strength steel composite galvanized plate resistant to spot weld LME cracking, comprising a high-strength steel body (1), a mild steel composite layer (2) and a galvanized layer (3), wherein two mild steel composite layers (2) are composite-rolled onto two surfaces of the high-strength steel body (1), respectively, and a galvanized layer (3) is formed on at least one surface of the mild steel composite layer (2) to form a high-strength steel composite galvanized plate.
2. The high strength steel body (1) is a high strength steel sensitive to spot weld LME and has a tensile strength of ≧780 MPa, preferably ≧980 MPa, more preferably ≧1180 MPa, preferably the tensile strength of the high strength steel is 780-1500 MPa, preferably 1180-1500 MPa.
3. The high strength steel composite galvanized sheet resistant to spot weld LME cracking according to claim 2, characterized in that the high strength steel contains, in mass percent, C≧0.1%, for example C≧0.14%, Mn≧1.0%, for example Mn≧1.5%, Si≧0.07%, preferably Si≧0.4%, preferably the high strength steel contains, in mass percent, C: 0.14-0.60%, Mn: 1.5-16%, Si: 0.07-2.0%, more preferably the high strength steel contains, in mass percent, C: 0.14-0.30%, Mn: 1.5-3.5%, Si: 0.4-2.0%.
4. The high-strength steel composite galvanized sheet resistant to spot weld LME cracking according to claim 2, characterized in that the high-strength steel contains, in mass percent, C: 0.1 to 0.3%, Si: 0.4 to 2.50%, Mn: 1.0 to 11.0%, and Al: 0 to 2.0%.
5. The high strength steel composite galvanized sheet resistant to spot weld LME cracking according to claim 2, characterized in that the high strength steel is selected from one or more of QP steel, TRIP steel, DH steel, 7Mn steel, 10Mn steel and MS steel.
6. The high-strength steel composite galvanized sheet resistant to spot-weld LME cracking according to any one of claims 1 to 5, characterized in that the mild steel composite layer (2) is mild steel that is insensitive to spot-weld LME, the mild steel containing C and Mn, and in mass percent, the C content is ≦0.1%, the Mn content is ≦1.1%, for example Mn ≦0.7%, and the tensile strength is ≦590 MPa, for example 150 to 590 MPa or 150 to 340 MPa, and preferably, in mass percent, the mild steel contains C: 0.001 to 0.1% and Mn: 0.1 to 1.1%.
7. The mild steel contains, in mass percent, C: 0.001-0.1%, Si: 0.001-0.50%, Mn: 0.1-0.1.1%, Nb: 0-0.02%, Ti: 0-0.025%, Ni: 0-0.025%, Cr: 0-0.05%, P: ≦0.05%, and the balance being Fe and unavoidable impurities. Alternatively, the mild steel contains, in mass percent, C: 0.0 7. The high strength steel composite galvanized sheet resistant to spot weld LME cracking according to claim 6, characterized in that it contains: 0.01-0.08%, Si: 0.001-0.05%, Mn: 0.1-0.7%, Nb: 0-0.02%, Ti: 0-0.025%, Ni: 0-0.025%, Cr: 0-0.05%, P: ≦0.05%, and the remainder being Fe and unavoidable impurities.
8. 7. The high strength steel composite galvanized sheet resistant to spot weld LME cracking according to claim 6, wherein the mild steel is selected from one or more of IF steel, aluminum killed steel, cold rolled carbon structural steel, phosphorus-added high strength steel, bake hardening steel and low alloy steel.
9. The high strength steel composite galvanized sheet resistant to spot weld LME cracking according to claim 1, characterized in that a relationship between a green slab thickness of the high strength steel body (1) and a green slab thickness of the mild steel composite layer (2) satisfies L×A+M×B+N×C=T. Here, A is the ratio of the green slab thickness of one mild steel composite layer (2) to the green slab thickness, C is the ratio of the green slab thickness of the other mild steel composite layer (2) to the green slab thickness, and B is the ratio of the green slab thickness of the high strength steel body (1) to the green slab thickness, where A+B+C=100%. The green slab is the total thickness of the green slabs of the high strength steel body (1) and the two mild steel composite layers (2). L is the tensile strength of one mild steel composite layer (2) after annealing, N is the tensile strength of the other mild steel composite layer (2) after annealing, and M is the tensile strength of the high strength steel body (1) after annealing. T is the target tensile strength of the high strength steel composite galvanized plate. Here, the unit of the tensile strength is MPa, and the unit of the thickness is microns.
10. The high strength steel composite galvanized plate resistant to spot weld LME cracking according to claim 9, characterized in that the values of A:B and C:B are in the range of 1:35.5 to 1:
5.
11. A high strength steel composite galvanized plate resistant to spot weld LME cracking according to any one of claims 1 to 10, characterized in that: In the high-strength steel composite galvanized plate, the thickness of each mild steel composite layer (2) is 10 to 200 μm, and / or In the high strength steel composite zinc-plated sheet, the thickness of the zinc-plated layer (3) is 4 to 26 μm.
12. The resistance of the high-strength steel composite galvanized sheet to spot welding LME cracking means, in a joint after the generation of welding spatter, that there is no LME crack in the joint before the generation of welding spatter, that there are no Type A LME cracks whose length does not exceed 10% of the plate thickness and the number of LME cracks does not exceed 6, that there are no Type D LME cracks whose length does not exceed 3% of the plate thickness and the number of LME cracks does not exceed 3, and that there are no Type B or Type C LME cracks in the joint after the generation of welding spatter.
13. A method for preparing a high strength steel composite galvanized sheet resistant to spot weld LME cracking according to any one of claims 1 to 12, comprising the steps of: Step 1: Take a green slab of high strength steel body (1) and a green slab of two mild steel composite layers (2), attach the green slabs of the two mild steel composite layers (2) to two surfaces of the green slab of high strength steel body (1), and weld the ends of the green slabs of the two mild steel composite layers (2) to the ends of the green slab of high strength steel body (1) to form a composite slab. Step 2: The composite slab is heated through a thick plate dividing process to reduce its thickness, and then subjected to initial rolling. Thereafter, the raw slab of the high-strength steel body (1) and the raw slab of the two mild steel composite layers (2) are metallurgically joined together to form a slug with tensile strength T. Step 3: Coat at least one side of the slug with a zinc-plated layer (3) to form a high-strength steel composite zinc-plated plate.
14. 14. The method according to claim 13, characterized in that in step 1, the lamination surfaces of the high strength steel body (1) and the two mild steel composite layers (2) need to be sanded and cleaned before the green slab of the two mild steel composite layers (2) is laminated with the green slab of the high strength steel body (1).
Citation Information
Patent Citations
Method for the production of motor vehicle components protected against corrosion
EP3243913A1
Composite steel material for welded structure finished by hot dip galvanizing
JP1986149468A
Manufacture of galvanized high tensile strength clad steel sheet
JP1992236749A
Steel strip composite material and method for manufacturing the same
JP2014501841A
Steel material having high toughness, and manufacturing method therefor
JP2018204077A